«Caste» and Education in 19th-Century Europe: Toward a Transnational History of Educational Inequality - Caruso, Marcelo (Historia y Memoria de la Educación, 2025)
The article analyses the use of a non-European conceptual system, the Indian and South Asian caste system and its essentialised differences, as a semantic resource through which European educationalists, teachers, inspectors and politicians expressed ideas of intense and persistent inequality. On the basis of a sample of Western and Central European pedagogical manuals and educational policy materials, several strands of the use of this vocabulary of inequality in nineteenth-century European discussion are shown: a civilisational strand that identified caste as something purely from an unequal past; a secularist strand in which the term caste was reserved for the priesthood; a strand linked to the critique of the widespread pauperism of the nineteenth century. These European uses of the conceptual field that includes caste, Brahmins and outcasts show a reductionism in the use of this field of meanings as a function of designating intense inequalities that had been in focus in the Enlightenment critiques against the state society. In this sense, the analysis advances a first advance on transnational frameworks in nineteenth-century educational discussions and shows an example of a transnational conceptual history.